Role of Military as the Guardian of Democracy in Pakistan - Iram Khalid and Zahid Yaseen (Journal of Political Studies, 2015)
This article investigates the role of military in the politics of Pakistan. The researcher highlights how our politicians have always been unable to develop a political culture on democratic parameters in the country. Side by side the masses start lacking trust in the politicians and political setup for their authoritarian attitude and inheritor leadership. Our political parties, no doubt, have good shows in the case of local leaders but unluckily they have been lethargic in giving birth to the leaders of national and international caliber. This factor creates gaps for military to enter politics and stay there under the very doctrine of ‘necessity’. Since the very early days of our emergence on the globe of the world, there has been a misconception that military may align all the disorders and civil institutions are not allowed to promote but in fact military did some better than these politicians. The research is based on the analysis of the authentic material in the form of literature in comparative politics, institutional theory, as well as civil military relations and political sector reforms. Through the conceptualization of the data, the researchers have developed thier stance that if our politicians learn to make decisions wisely like those of India, the results would be far better and healthier as both states got independence on the same turn of the history.